Removal of congo red and acid yellow 36 dye using orange peel and rice husk as absorbent - Ranjini K. Nagarajah (2013)
Many researchers have identified capability of agricultural wastes as absorbents to remove many types of pollutants including dyes. This study represents the use of orange peel (OP) and rice husk (RH) to remove two types of dye, congo red (CR) and acid yellow 36 (AY 36) dyes and makes a simple comparison among granular form of OP, RH and activated form of OP, RH. Both type of dyes are toxic and can cause severe problems to the environment. Factors such as absorbent dosage were studied. Batch absorption studies were conducted at 27°C with constant stirring at 150 rpm for 2 hours and absorbent dosage of (0.2 — 1.0 g). The result show that the activated form of OP and RH has the highest removal percentage of dye CR and AY 36 which are up to 100% removal. This study indicates that the OP and RH could be employed as a low cost material for the removal of the textile dyes from effluents.